Casos y cosas: semanario popular (Vol. 2, No. 47) - Imprenta La Region (My University, 1920)
SPANISH: Incluye: Revelaciones..... Desde mi tribuna, Apuntes de un ocioso, Correo franco y con franqueza, Un subterraneo?, Femeninas

ENGLISH: Revelations..... From my rostrum, notes of an idle, frank and frank mail, a subway?, feminine
Cases and things: popular weekly (Vol. 2, No. 47)
Keywords: Periodicals; Satire, Peruvian; Humor; Iquitos (Perú)--revistas; Perú--revistas satíricas